Efektivitas Pendayagunaan Zakat Produktif Pada Pemberdayaan Ekonomi Di LAZISMU Kota Medan - Muhammad Arifin Lubis (Yayasan Rahmat Islamiyah, 2022)
This research is a qualitative descriptive study which aims to determine the effectiveness of productive zakat utilization in economic empowerment of mustahik. Data collection techniques using observation, interviews, and documentation. From the results of the study, it can be concluded that the concept of productive zakat utilization in mustahik economic empowerment carried out by LAZISMU Medan City is poured into several programs, namely in the form of providing business capital / business assistance both individually and in groups, providing job skills training, and providing work tools assistance. As for the effectiveness indicators using the theory of Ni Wayan Budiani, namely: accuracy of program targets, program socialization, program objectives, and program monitoring. The results of this study indicate that the indicators of the accuracy of the program targets and have been effective. Meanwhile, indicators of program socialization, program monitoring, and program objectives can be said to have not been effective.